The Value of Graft Implantation Sequence in Simultaneous Pancreas-Kidney Transplantation on the Outcome and Graft Survival - Hau, Hans-Michael (J Clin Med, 2021)
Background/Objectives: The sequence of graft implantation in simultaneous pancreas-kidney transplantation (SPKT) warrants additional study and more targeted focus, since little is known about the short- and long-term effects on the outcome and graft survival after transplantation. Material and methods: 103 patients receiving SPKT in our department between 1999 and 2015 were included in the study. Patients were divided according to the sequence of graft implantation into pancreas-first (PF, n = 61) and kidney-first (KF, n = 42) groups. Clinicopathological characteristics, outcome and survival were reviewed retrospectively. Results: Donor and recipient characteristics were similar. Rates of post-operative complications and graft dysfunction were significantly higher in the PF group compared with the KF group (episodes of acute rejection within the first year after SPKT: 11 (18%) versus 2 (4.8%); graft pancreatitis: 18 (18%) versus 2 (4.8%), p = 0.04; vascular thrombosis of the pancreas: 9 (14.8%) versus 1 (2.4%), p = 0.03; and delayed graft function of the kidney: 12 (19.6%) versus 2 (4.8%), p = 0.019). The three-month pancreas graft survival was significantly higher in the KF group (PF: 77% versus KF: 92.1%; p = 0.037). No significant difference was observed in pancreas graft survival five years after transplantation (PF: 71.6% versus KF: 84.8%; p = 0.104). Kidney graft survival was similar between the two groups. Multivariate analysis revealed order of graft implantation as an independent prognostic factor for graft survival three months after SPKT (HR 2.6, 1.3–17.1, p = 0.026) and five years (HR 3.7, 2.1–23.4, p = 0.040). Conclusion: Our data indicates that implantation of the pancreas prior to the kidney during SPKT has an influence especially on the early-post-operative outcome and survival rate of pancreas grafts.